La lógica del nudo borromeo: un paradigma del corte estructural notas para una filosofía psicoanalítica - Farrán, Roque (Nómadas. Critical Journal of Social and Juridical Sciences, 2009)
The principal idea that guides this article is to interrogate to what point the last lacanian elaborations, concerning the borromean knot, agree or not to an epistemological break with regard to the Freudian classic theory. A basic place will occupy in this investigation the concept of real consistency examined by Lacan from the knotting of three registers (RSI): real, symbolic, imaginary. That is to say, where the real will not be thought in its relative autonomy with regard to other two registers, as it was treated in the first part of his teaching (50 ’ and 60 ’), but in the effective joint of the three (70 ’).